1998
DOI: 10.1074/jbc.273.17.10733
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Protein

Abstract: Multidrug resistance protein (MRP) is a broad specificity, primary active transporter of organic anion conjugates that confers a multidrug resistance phenotype when transfected into drug-sensitive cells. The protein was the first example of a subgroup of the ATP-binding cassette superfamily whose members have three membrane-spanning domains (MSDs) and two nucleotide binding domains. The role(s) of the third MSD of MRP and its related transporters is not known. To begin to address this question, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 40 publications
(67 reference statements)
6
60
0
Order By: Relevance
“…It has been reported previously that co-expression of the MSD1 (MRP1 281N ) and the carboxyl-terminal core domain molecule of MRP1 can generate functional molecules, whereas the core domain alone is not functional (19,20). The results in Fig.…”
Section: Effect Of Mutations Of Cys 7 and Cys 32 On Human Mrp1-mediatsupporting
confidence: 67%
See 2 more Smart Citations
“…It has been reported previously that co-expression of the MSD1 (MRP1 281N ) and the carboxyl-terminal core domain molecule of MRP1 can generate functional molecules, whereas the core domain alone is not functional (19,20). The results in Fig.…”
Section: Effect Of Mutations Of Cys 7 and Cys 32 On Human Mrp1-mediatsupporting
confidence: 67%
“…These observations suggest that the folding of MSD1 is different in the absence and presence of the core domain. It has been shown previously that functional MRP1 was produced when the MSD1 and the core domain were co-expressed (19). We thus conclude that the folding of the MSD1 in the presence of the core domain is likely correct and that the folding of MSD1 in the absence of the core domain is incorrect, which results in the formation of intermolecular disulfide bonds.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Notwithstanding evidence indicating that N-terminal deletion of the entire MSD0 does not alter several properties of the pump, it is anticipated that this domain has functions that have yet to be uncovered. Studies showing that MRP1 activity can be affected by point mutations in the extracellular portion of the N-terminus and in MSD0, and by N-terminal deletions that extend to and include the first transmembrane domain hint at this possibility, although it remains to be determined whether these perturbations influence actual drug binding and transport as opposed to preventing the assumption of correct topology in the plasma membrane (Gao et al, 1998;Yang et al, 2002;Leslie et al, 2003b).…”
Section: Mrp1mentioning
confidence: 99%
“…Previous studies have shown that portions of the first 280 amino acids of MRP1 encompassing the N-terminal MSD (MSD1) and the cytoplasmic loop connecting it to the second MSD (MSD2) are important for its expression in mammalian cell membranes as well as its ability to transport at least some of its substrates (32,33). In the course of a mutational analysis of this region of MRP1, we derived a mutant in which Pro 196 was replaced with Ala by site-directed mutagenesis (34).…”
Section: Drug Resistance Is Lost and Accumulation Is Restored Inmentioning
confidence: 99%